Immunization of LDL receptor-deficient mice with β2-glycoprotein 1 or human serum albumin induces a more inflammatory phenotype in atherosclerotic plaques - Dunoyer-Geindre, Sylvie; Kwak, Brenda R.; Pelli, Graziano; Roth, Isabelle; Satta, Nathalie; Fish, Richard J.; Reber, Guido; Mach, François; Kruithof, Egbert K. O.; de Moerloose, Philippe (Thrombosis and Haemostasis, 2007)
Antiphospholipid antibodies are a risk factor for venous and arterial thrombosis and may contribute to the development of atherosclerosis. The aim of this study was to investigate whether antibodies to human β2-glycoprotein 1 (β2 GP1), as a model of antiphospholipid antibodies, modify the phenotype of atherosclerotic lesions. LDL receptor-deficient mice were immunized with human β2 GP1, human serum albumin (HSA), or not immunized, and fed a high-cholesterol diet for 14 weeks. Some mice also received pravastatin. Immunization with human β2 GP1 or HSA resulted in formation of autoantibodies recognizing murine β2 GP1 or murine albumin, respectively. We quantified atherosclerotic lesion development and mRNA levels of inflammationassociated proteins in the thoraco-abdominal aorta as well as lesion development, cellular composition and collagen content in the aortic roots. Immunization with β2 GP1 or HSA had no effect on lesion size, but modified the expression in plaque areas of several inflammation-associated proteins. Expression of matrix metalloproteinase-9, tissue factor, interferon-gamma and CD25 was highest in the thoraco-abdominal aorta of β2 GP1-immunized mice, lowest in non-immunized mice and intermediate in HSA-immunized animals. Immunization with β2 GP1, but not HSA, resulted in a lower smooth muscle cell and collagen content of lesions in aortic roots. Statin treatment partially reversed the effects of β2 GP1 immunization. We conclude that immunization with β2 GP1, and to a lesser extent with HSA, leads to modifications in the cellular and protein composition of atherosclerotic plaques, which are associated with a more inflammatory phenotype. Statin treatment partially prevents these changes.
Keywords: Antiphospholipid antibodies; atherosclerosis; β2-glycoprotein 1; immunization; statins